Attenuated cell cycle and DNA damage response transcriptome signatures and overrepresented cell adhesion processes imply accelerated progression in patients with lower-risk myelodysplastic neoplasms - Kaisrlikova, Monika; Kundrat, David; Koralkova, Pavla; Trsova, Iva; Lenertova, Zuzana; Votavova, Hana; Merkerova, Michaela Dostalova; Krejcik, Zdenek; Vesela, Jitka; Vostry, Martin; Simeckova, Radka; Markova, Marketa Stastna; et al. (International journal of cancer, 2024)
Patients with myelodysplastic neoplasms (MDS) are classified according to the risk of acute myeloid leukemia transformation. Some lower-risk MDS patients (LR-MDS) progress rapidly despite expected good prognosis. Using diagnostic samples, we aimed to uncover the mechanisms of this accelerated progression at the transcriptome level. RNAseq was performed on CD34+ ribodepleted RNA samples from 53 LR-MDS patients without accelerated progression (stMDS) and 8 who progressed within 20 months (prMDS); 845 genes were differentially expressed (ІlogFCІ > 1, FDR < 0.01) between these groups. stMDS CD34+ cells exhibited transcriptional signatures of actively cycling, megakaryocyte/erythrocyte lineage-primed progenitors, with upregulation of cell cycle checkpoints and stress pathways, which presumably form a tumor-suppressing barrier. Conversely, cell cycle, DNA damage response (DDR) and energy metabolism-related pathways were downregulated in prMDS samples, whereas cell adhesion processes were upregulated. Also, prMDS samples showed high levels of aberrant splicing and global lncRNA expression that may contribute to the attenuation of DDR pathways. We observed overexpression of multiple oncogenes and diminished differentiation in prMDS; the expression of ZEB1 and NEK3, genes not previously associated with MDS prognosis, might serve as potential biomarkers for LR-MDS progression. Our 19-gene DDR signature showed a significant predictive power for LR-MDS progression. In validation samples (stMDS = 3, prMDS = 4), the key markers and signatures retained their significance. Collectively, accelerated progression of LR-MDS appears to be associated with transcriptome patterns of a quiescent-like cell state, reduced lineage differentiation and suppressed DDR, inherent to CD34+ cells. The attenuation of DDR-related gene-expression signature may refine risk assessment in LR-MDS patients.
Keywords: accelerated progression; transkriptom; Neoplasms; Myelodysplastic Syndromes; transcriptome; tumorigenesis barrier; Transcriptome; kinasy NEK; NIMA-Related Kinases; MDS; buněčná adheze; myelodysplastické syndromy; DNA Repair; oprava DNA; lidé; Humans; Cell Cycle; lower-risk; nádory; buněčný cyklus; Cell Adhesion